Alexithymia and pain experience among patients using methadone-maintenance therapy. (1st January 2021) - Morie, Kristen P.; Potenza, Marc N.; Beitel, Mark; Oberleitner, Lindsay M.; Roos, Corey R.; Yip, Sarah W.; Oberleitner, David E.; Gaeta, Marina; Barry, Declan T.
Highlights: We explored alexithymia and pain in patients in treatment for opioid use disorder. Alexithymia was associated with greater pain interference and pain catastrophizing. Increased alexithymia was associated with reduced pain acceptance. Alexithymia contributes to pain interference and may be a therapeutic target. Pain catastrophizing and acceptance mediated effects of alexithymia on interference. Abstract: Background: Alexithymia, difficulty identifying and describing one's emotions coupled with a tendency to externalize, is a potentially important yet understudied treatment target for patients with opioid use disorder. The aim of this study was to examine the role of alexithymia in pain experience among individuals with opioid use disorder. Methods: One-hundred-and-sixty-four patients receiving methadone maintenance treatment completed a battery of self-report measures related to alexithymia, drug use, and pain experiences. Comparisons were performed on the full sample between those with or without clinically significant levels of alexithymia. For a subsample reporting pain (n = 138), intercorrelations were performed to test whether drug use history, pain catastrophizing, pain acceptance, and alexithymia were related to pain severity and pain interference. Regression analyses were performed to test for serial mediation of pain catastrophizing and pain acceptance on the relationship between alexithymia and pain interference in this subsample. Results: Individuals with alexithymia showed increased pain catastrophizing and interference, and intercorrelations indicated that increased alexithymia was associated with increased pain interference, more pain catastrophizing, and reduced pain acceptance. A serial regression model among a subset of patients with pain indicated that pain catastrophizing and pain acceptance mediated the effect of alexithymia on pain interference. Conclusions: These findings suggest that alexithymia, as well as both pain catastrophizing and pain acceptance, contribute to interference associated with pain and are potentially important intervention targets among methadone-treated patients with pain.